2017
DOI: 10.1371/journal.pone.0189966
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of magnesium sulphate use in women hospitalized at <29 weeks with severe or non-severe pre-eclampsia

Abstract: ObjectiveMagnesium sulphate is recommended by international guidelines to prevent eclampsia among women with pre-eclampsia, especially when it is severe, but fewer than 70% of such women receive magnesium sulphate. We aimed to identify variables that prompt Canadian physicians to administer magnesium sulphate to women with pre-eclampsia.MethodsData were used from the Canadian Perinatal Network (2005–11) of women hospitalized at <29 weeks’ who were thought to be at high risk of delivery due to pre-eclampsia (us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, the clinical effect of single use is not good because severe placental ischemia and hypoxia will lead to maternal endothelial dysfunction [17]. Studies have found that giving a scientific dose of magnesium sulfate for preeclampsia maternity can reduce the incidence of Evidence-Based Complementary and Alternative Medicine cerebral palsy in children [18]. However, Ugwu et al reported that long-term application of magnesium sulfate has the risk of magnesium ion poisoning, which is not conducive to maternal and child health [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical effect of single use is not good because severe placental ischemia and hypoxia will lead to maternal endothelial dysfunction [17]. Studies have found that giving a scientific dose of magnesium sulfate for preeclampsia maternity can reduce the incidence of Evidence-Based Complementary and Alternative Medicine cerebral palsy in children [18]. However, Ugwu et al reported that long-term application of magnesium sulfate has the risk of magnesium ion poisoning, which is not conducive to maternal and child health [19].…”
Section: Discussionmentioning
confidence: 99%
“…20 Alternative dosage regimens of MgSO 4 are also being evaluated. 21,22 Despite strong evidence of effectiveness and costeffectiveness, MgSO 4 is often underused for these indications, 13,[23][24][25] particularly in LMICs. 26 Previous research has explored factors affecting MgSO 4 guideline implementation, identifying system and market failures that restrict drug availability, absence of clinical protocols and staff reluctance.…”
Section: Introductionmentioning
confidence: 99%
“…Severe PE may even bring damage to organs ( 1 , 2 ). At present, the pathogenesis of PE is still unclear, and most scholars believe that PE is caused by systemic vascular endothelial injury after placental pathophysiological changes ( 3 , 4 ). The pathogenesis of PE is also very complex, and may be associated with placental ischemia, genetic predisposition, immune adaptation and oxidative stress response ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%